The Notion of causative at Shirazi (Damascus University Journal for legal sciences, 2025)
This Sadr al-Din Shirazi was not the first philosopher to discuss the issue of existence, but he was able to build anew trend of philosophy of existence and theory of a complete and unique in a differ and unique and characterized by creativity and renewal the Rashdip and through the history Islamic philosophy and he raised this issue radically different from the mainstream and Al - sinawi . By the aim of the research to show the attitude of speakers for the meaning of   causative and their criticism and Is this criticism a natural result to their Goddess researches ? Or is isitafirst Knawiny Pasition for this concept ?The research will try to discover The history of Philosophic attitude of the causative by AL-Ashaara and to show is this concept complicated through. its varied logical and Antilogy metaphysics indicators according to  level , Here Point show the Position of Speakers Poets Through the nature  , and to show the history of  AL-Ashaara , terature concept itself through Showing the development of speech inside this speech school Philosophic are these speakers result of Greek effects or are these  result of idealistic Idiologic differences in understand - inc  the  religious text itself.
Keywords: Causality; Cause; Effect; Breasts